Ancestral sequence reconstruction of ancient lipase from family I.3 bacterial lipolytic enzymes - Mohd Rozi, Mohamad Farihan Afnan; Raja Abd. Rahman, Raja Noor Zaliha; Thean, Adam Chor Leow; Mohamad Ali, Mohd Shukuri (Elsevier, 2022)
Family I.3 lipase is distinguished from other families by the amino acid sequence and secretion mechanism. Little is known about the evolutionary process driving these differences. This study attempt to understand how the diverse temperature stabilities of bacterial lipases from family I.3 evolved. To achieve that, eighty-three protein sequences sharing a minimum 30% sequence identity with Antarctic Pseudomonas sp. AMS8 lipase were used to infer phylogenetic tree. Using ancestral sequence reconstruction (ASR) technique, the last universal common ancestor (LUCA) sequence of family I.3 was reconstructed. A gene encoding LUCA was synthesized, cloned and expressed as inclusion bodies in E. coli system. Insoluble form of LUCA was refolded using urea dilution method and then purified using affinity chromatography. The purified LUCA exhibited an optimum temperature and pH at 70 ℃ and 10 respectively. Various metal ions increased or retained the activity of LUCA. LUCA also demonstrated tolerance towards various organic solvents in 25% v/v concentration. The finding from this study could support the understanding on temperature and environment during ancient time. In overall, reconstructed ancestral enzymes have improved physicochemical properties that make them suitable for industrial applications and ASR technique can be employed as a general technique for enzyme engineering.